Unveiling the potential of calcium chloride for Botrytis blight management in cut roses using untargeted metabolomics analysis - Melissa Muñoz; William C. Bridges; Christopher A. Saski; Guido Schnabel; James E. Faust (Postharvest Biology and Technology, 2025)

Is sexual size dimorphism in walleye, Sander vitreus , a driver of seasonal movements in Lake Erie? - Christian J. Bihun; Matthew D. Faust; Richard T. Kraus; Thomas M. MacDougall; Jason M. Robinson; Christopher S. Vandergoot; Graham D. Raby (Journal of Fish Biology, 2025)
Walleye ( Sander vitreus ) are a sexually dimorphic species in which females are larger than males in adulthood. Walleye can also exhibit sex‐ and population‐based differences in migration behavior. In Lake Erie, we used acoustic telemetry to test the prediction that female walleye exhibit larger broad‐scale movements than males during the summer and autumn. This prediction was based on the hypothesis that greater foraging in females would be needed to satisfy their higher energy requirements. We quantified movements of males and females from distinct spawning populations from Lake Erie's west and east basins using a lake‐wide grid of acoustic receivers in 2017 and 2018. We found no differences between male and female home range sizes, core range sizes, or distances travelled in either population. Fish length‐at‐tagging was unrelated to the size of a fish's home range or to its distance travelled, contrary to previous predictions about body size as a driver of migration distance in the Lake Erie population. We found that west basin walleye occupied large and indiscrete portions of the lake, but the core range of females extended into the central basin, whereas males were concentrated in the west basin. Walleye originating from the east basin confined their movements primarily to the east basin and showed stronger home range overlap among members of their population than did walleye from the west basin population. Within either population, walleye had more home range overlap with members of the same sex, which likely reflects differences in the migratory tendencies of males and females.

Drivers and timing of grass carp movement within the Sandusky River, Ohio: implications to potential spawning barrier response strategy - Justin J. Bopp; Travis O. Brenden; Matthew D. Faust; Christopher S. Vandergoot; Richard T. Kraus; James J. Roberts; Lucas R. Nathan (Biological Invasions, 2023)

Cardiac activity in walleye ( Sander vitreus ) during exposure to and recovery from chemical anaesthesia, electroanaesthesia and electrostunning - Connor H. Reid; Graham D. Raby; Matthew D. Faust; Steven J. Cooke; Christopher S. Vandergoot (Journal of Fish Biology, 2022)
Handling and conducting invasive procedures are necessary for aspects of fisheries science, invariably inducing a stress response and imposing energetic demands on fish. Anaesthesia or immobilisation techniques are often used in an attempt to mitigate stress and improve welfare, yet these also come with their own impacts on post‐release recovery. Here, the authors investigated whether changes in cardiac activity (heart rates over time, heart rate maxima, and scopes) differed in adult walleye ( Sander vitreus ) anaesthetised with AQUI‐S® 20E (eugenol), electroanaesthetised with a transcutaneous electrical nerve stimulation (TENS) unit or electrostunned with a commercially developed stunning unit. This experiment was divided into two trials. In the first trial, fish were implanted with heart rate loggers and left to recover for c. 4 days. In the second trial, fish were implanted with heart rate loggers, given 3 days to recover and re‐exposed to their initial treatments (excluding surgery). Post‐treatment cardiac activity was quantified for both trials. Although highly variable across individuals, the authors found no significant differences in heart rate changes over time or recovery times among treatments. Maximum heart rates were consistent among treatment groups, yet significant differences in heart rate scope provided further evidence of strong interindividual variation in the second trial. Based on these results, the authors did not identify any welfare‐relevant differences or concerns associated with one treatment over another. Further investigations of the relationships between measures of cardiac function and other physiological stress markers would be beneficial towards identifying best practices for fish handling in fisheries science.

Climate shifts vs. edaphic humidity and the difficulty of palaeoreconstructions – a malacological study on stable isotopes in Quaternary dune sequences of Fuerteventura - Christiane Richter; Christopher‐Bastian Roettig; Daniel Wolf; Andreas Gärtner; Thomas Kolb; Dominik Faust (Journal of Quaternary Science, 2021)
Dune palaeosurface sequences on the Eastern Canary Islands were investigated for stable isotope records in gastropod shells of the genus Theba . Due to the ecology of the taxon and the special oceanic insularity of the study site, we assume that δ 18 O shell signals in our case mainly reflect shifts in δ 18 O signals of sea surface water. We found that a rapid decrease in δ 18 O shell signals is associated with significant changes in gastropod associations. We suggest that these faunal changes were caused by strong (hot) winds at the end of glacial phases, that were described previously by Moreno et al . In addition, we assume that rapid declines in δ 18 O shell signals due to marine transgressions were followed by geomorphologically stable phases, dominated by dust enrichment. Such palaeosurfaces correlate with maxima of gastropod biodiversity and with more negative δ 13 C shell signals indicating a higher proportion of C3 plants. Based on our results, we also assume that these silty palaeosurfaces were associated with increased soil moisture conditions due to a higher water storage capacity of the finer substrate, independent of climatic moisture conditions.

Rock magnetics of carbonate systems–investigating palaeodune archives on Fuerteventura (Canary Islands) - Florian Schneider; Christopher‐Bastian Roettig; Daniel Wolf; Philipp Baumgart; Ulrich Hambach; Dominik Faust (Journal of Quaternary Science, 2020)
The mineral magnetic properties of Pleistocene aeolian dune sands from the island of Fuerteventura (Canary Islands, Spain) were studied in order to reconstruct the palaeoenvironmental evolution of Pleistocene climates during their formation. The palaeodunes on Fuerteventura mainly consist of carbonate sands admixed with dust and material of volcanic origin. Due to the low magnetic background caused by the diamagnetic character of carbonate sands, these archives offer a lot of potential for environmental magnetic studies to detect the imprint of dust, volcanic material and paedogenesis. Four sections of alternating palaeosurface–aeolianite sequences in palaeodune fields have been analysed by means of extensive rock magnetic measurements. These Quaternary archives consist of deposits originating from different sources. I. material blown from the shallow shelf, II. material of volcanic origin, and III. long‐range transported dust. The rock magnetic findings enable a more detailed interpretation of the palaeosurfaces within the sequences. We are able to differentiate semiquantitatively between the different source materials on one hand and to distinguish on the other hand those from soil‐forming processes. Soil formation is only weakly developed in the dust imprints in the palaeosol aeolianite sequences, linked to sparse vegetation cover during the Pleistocene on Fuerteventura.

Plant composition and diversity in a semi-natural Mediterranean island landscape: the importance of environmental factors - Tim Drissen; Christopher Faust; Robin Stadtmann; Julia T. Treitler; Stefan Zerbe; Jasmin Mantilla-Contreras (Plant Biosystems, 2019)

Endoscopy-guided orthotopic implantation of colorectal cancer cells results in metastatic colorectal cancer in mice - Dominik Bettenworth; Marcus M. Mücke; Katrin Schwegmann; Andreas Faust; Christopher Poremba; Michael Schäfers; Dirk Domagk; Philipp Lenz (Clinical & Experimental Metastasis, 2016)

Odor transport in turbulent flows: Constraints on animal navigation - Christopher M. Finelli; N. Dean Pentcheff; Richard K. Zimmer-Faust; David S. Wethey (Limnology and Oceanography, 1999)
Odor plumes are common features of aquatic and terrestrial environments, forming an olfactory landscape through which animals must navigate to locate resources and avoid potential hazards. Time‐averaged concentration profiles suggest that plumes consist of stable gradients in odor that animals may use for orientation. However, the time scales necessary to generate such profiles are much longer than those typically associated with the neural or behavioral components of odor‐mediated search. In contrast, plume measurements made at biologically relevant scales have indicated that turbulent plumes consist of discrete odor filaments separated by clean water. In addition, certain characteristics of individual odor filaments may vary consistently with distance from the odor source, thus providing directional information to a navigating organism. Unfortunately, there is no method to predict the distribution of these putative chemical cues, and our knowledge of odor dispersal is limited to very few laboratory flume studies. Here, we present the results of a field study during which we measured the distributions of the time‐averaged concentration, properties of odor filaments, conditional statistics, and relevant hydrodynamic mixing parameters. Many of the observed odor plume characteristics have similar spatial distributions through a range of hydrodynamic conditions. The high degree of similarity in the distribution of many odor plume characteristics suggests that organisms can rely on any number of metrics to successfully orient in an odor plume. However, the temporal and spatial scales of odor dispersal may constrain the strategies used by navigating organisms and influence the efficiency of odor‐mediated search. These field results should provide the basis for further empirical and theoretical work on chemosensory‐mediated behavior of aquatic animals.